Pengaruh Media Puzzle terhadap Hasil Belajar IPAS Materi Kekayaan Budaya Indonesia Siswa Kelas IV SDN Karang Mulya 1 - Qur’ani, Fathiya Cahaya; Rosnaningsih, Asih; Amaliyah, Aam (FONDATIA, 2025)
This study is motivated by the low academic achievement of students in the IPAS subject, particularly in the theme of Indonesian cultural wealth, as well as the limited use of creative learning media at the elementary school level. The purpose of this research is to evaluate the impact of using puzzle media on the learning outcomes of fourth-grade students at SDN Karang Mulya 1. A quantitative approach with a quasi-experimental method and purposive sampling technique was employed, involving two class groups: IVA as the experimental group and IVC as the control group, each consisting of 30 students. The research instrument consisted of 25 validated multiple-choice questions. Data were analyzed using the t-test. The results show no significant difference in the pre-test scores of the two groups; however, a significant difference was found in the post-test scores after the treatment, with t-count (2.067) > t-table (2.001). These findings indicate that the use of puzzle media has a positive impact on student learning outcomes. The study concludes that puzzle media can serve as an effective alternative for improving IPAS learning outcomes. The implications highlight the importance of innovative media in enhancing student participation and understanding, and provide a reference for the development of other contextual learning media in elementary education.